ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PERTANIAN KE LAHAN NON PERTANIAN DI KOTA KUPANG - Erastus D. Ngadi; Alfetri N. P. Lango; Lika Bernadina (Undana Press, 2021)
The purpose of this study was to determine how much influence the total population, number of industries, and GDP on the rate of conversion of agricultural land to non-agricultural land in Kupang City. This research uses quantitative research, the data is processed with the needs of the model used. The data source comes from the Kupang City Statistics Agency. The amount of research data used in this study is from 2010 - 2019. With processing techniques and using classical assumptions and hypothesis testing, as well as analyzing data using multiple linear regression with the help of Software Eviews 9 for windows. The results showed that the area of ​​conversion of agricultural land to non-agricultural land during the last 10 years has decreased from an area of ​​6,384 hectares with lowland rice production decreasing from 2,345.2 tons / hectare to 2,132 tons / hectare in 2019. population, number of industry, GRDP have a significant and positive effect on the conversion of agricultural land functions. And partially the population, number of industries, and GRDP have a significant and positive effect. Calculations are made to measure the proportion and percentage of the total variation in the dependent variable that can be explained by the regression model. From the regression results above, the value of R squared (R2) is 0.823999, this means that the independent variable explains the variation of the Change in Agricultural Land Functions in Kupang City by 82.39% while the remaining 17.61% is explained by other variables outside the study.